Neuronal hyperexcitability in the dorsal horn after painful facet joint injury - Quinn, Kyle P. (2010)
Excessive cervical facet capsular ligament stretch has been implicated as a cause of whiplash-associated disorders following rear-end impacts, but the pathophysiological mechanisms that produce chronic pain in these cases remain unclear. Using a rat model of C6/C7 cervical facet joint capsule stretch that produces sustained mechanical hyperalgesia, the presence of neuronal hyperexcitability was characterized 7 days after joint loading. Extracellular recordings of spinal dorsal horn neuronal activity between C6 and C8 (117 neurons) were obtained from anesthetized rats, with both painful and non-painful behavioral outcomes established by the magnitude of capsule stretch. The frequency of neuronal firing during noxious pinch (p<0.0182) and von Frey filaments applications (4–26 g) to the forepaw was increased (p<0.0156) in the painful group compared to the non-painful and sham groups. In addition, the incidence and frequency of spontaneous and afterdischarge firing were greater in the painful group (p<0.0307) relative to sham. The proportion of cells in the deep laminae that responded as wide dynamic range neurons also was increased in the painful group relative to non-painful or sham groups (p<0.0348). These findings suggest that excessive facet capsule stretch, while not producing visible tearing, can produce functional plasticity of dorsal horn neuronal activity. The increase in neuronal firing across a range of stimulus magnitudes observed at day 7 post-injury provides the first direct evidence of neuronal modulation in the spinal cord following facet joint loading, and suggests that facet-mediated chronic pain following whiplash injury is driven, at least in part, by central sensitization.